2019
DOI: 10.2217/nnm-2018-0500
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of low-cost Nanocarriers Produced By Green Synthesis: Macrophage Uptake of Superparamagnetic Iron Oxide Nanoparticles

Abstract: Aim: The primary goal of this work was to synthesize low-cost superparamagnetic iron oxide nanoparticles (SPIONs) with the aid of coconut water and evaluate the ability of macrophages to internalize them. Our motivation was to determine potential therapeutic applications in drug-delivery systems associated with magnetic hyperthermia. Materials & methods: We used the following characterization techniques: x-ray and electron diffractions, electron microscopy, spectrometry and magnetometry. Results: The synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 64 publications
3
19
0
Order By: Relevance
“…The characteristic blue color developing from the reaction of potassium ferrocyanide with NP ferric ions highlighted a comparable macrophage dose-dependent uptake of nanoconjugated antibiotics or of their nanocarriers in 24h. That macrophages engulfed IONPs, NP-TEICO, and NP-VANCO in a comparable mode confirmed what was already reported by other authors, i.e., that when macrophages are exposed in vitro to nanomaterials, they usually engulf them ( Qie et al, 2016 ; Verçoza et al, 2019 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The characteristic blue color developing from the reaction of potassium ferrocyanide with NP ferric ions highlighted a comparable macrophage dose-dependent uptake of nanoconjugated antibiotics or of their nanocarriers in 24h. That macrophages engulfed IONPs, NP-TEICO, and NP-VANCO in a comparable mode confirmed what was already reported by other authors, i.e., that when macrophages are exposed in vitro to nanomaterials, they usually engulf them ( Qie et al, 2016 ; Verçoza et al, 2019 ).…”
Section: Resultssupporting
confidence: 90%
“…We hereby reported that in vitro cultures of macrophages engulfed both bare and antibioticconjugated IONPs. This is not surprising since several studies have shown that macrophages internalize NPs (Verçoza et al, 2019), although, in principle, their surface modifications might allow evasion of phagocytic clearance (Qie et al, 2016). In any case, little is known about the in vivo recruitment of macrophages by nanomaterials and, a fortiori, by nanoantibiotics, depending again on their administration routes, body district distribution and physicochemical properties of their surface.…”
Section: Nanotoxicity Of Gpa-np Systemsmentioning
confidence: 99%
“…Coconut water also finds application in nanotechnology, more particularly in the synthesis of nanoparticles (NPs). Gold [39], silver [40], BaTiO 3 [41], Y 2 O 3 :Nd 3+ [42], and superparamagnetic iron oxide [43] NPs have been synthesized using coconut water.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite all their potential, the synthesis processes of the SPIONs are characterized by being expensive and toxic to humans and the environment [6]. In this scenario, our group demonstrated the therapeutic potential of low-cost biocompatible SPIONs produced by green synthesis [18]. Thus, the present study aimed to evaluate in vitro the therapeutic potential of SPIONs produced with coconut water to treat cutaneous leishmaniasis caused by Leishmania amazonensis.…”
Section: Discussionmentioning
confidence: 97%